Valorisation de la chenille comestible Bunaeopsis aurantiaca dans la gestion communautaire des forêts du Sud-Kivu (République Démocratique du Congo) - Muvundja Fabrice Amisi; Uwikunda Serondo Héritier; Mande Paul; Alunga Lufungula Georges; Balagizi Karhagomba Innocent; Isumbisho Mwapu Pascal (VertigO)
This study was conducted to evaluate the nutritional value of an edible caterpillar : Bunaeopsis aurantiaca, eaten by the riparian populations of the Congo basin forest, in general, and in South-Kivu forest regions in particular. This lepidoptera larvae, is naturally hosted by the tree Uapaca guineensis. This tree is known due to its precious wooden planks as well as a habitat of caterpillars. The results of the proximate analysis for its nutritional value composition revealed that this caterpillar is constituted by 49 % of total proteins, 24.2 of total lipids, 4.5 % of carbohydrates and 3.2 of total minerals compared to dry material samples. The energetic content of 100 g-sample of the caterpillar was estimated to 433 kcal. These results are comparable enough with the nutritional value of fish, especially the locally liked sardine Limnothrissa miodon. This work demonstrates that B. aurantiaca, like many other edible caterpillars, is a very good source of animal proteins, and hence, highly nutritive. The conservation of this non-timber resource should benefit of more attention from all stakeholders in order to guarantee its sustainability as well as different forest environmental services.